Occurrence and types of medication error and its associated factors in a reference teaching hospital in northeastern Iran: a retrospective study of medical records - Seyed Saeed Tabatabaee; Vahid Ghavami; Javad Javan-Noughabi; Edris Kakemam (BMC, 2022)
Abstract Background Medication errors are categorized among the most common medical errors that may lead to irreparable damages to patients and impose huge costs on the health system. A correct understanding of the prevalence of medication errors and the factors affecting their occurrence is indispensable to prevent such errors. The purpose of this study was to investigate the prevalence and types of medication errors among nurses in a hospital in northeastern Iran. Methods The present descriptive-analytical research was conducted on 147 medical records of patients admitted to the Department of Internal Medicine at a hospital in northeastern Iran in 2019, selected by systematic sampling. The data were collected through a researcher-made checklist containing the demographic profiles of the nurses, the number of doctor's orders, the number of medication errors and the type of medication error, and were finally analyzed using STATA version 11 software at a significance level of 0.05. Results Based on the findings of this study, the mean prevalence of medication error per each medical case was 2.42. Giving non-prescription medicine (47.8%) was the highest and using the wrong form of the drug (3.9%) was the lowest medication error. In addition, there was no statistically significant relationship between medication error and the age, gender and marital status of nurses (p > 0.05), while the prevalence of medication error in corporate nurses was 1.76 times higher than that of nurses with permanent employment status (IRR = 1.76, p = 0.009). The prevalence of medication error in the morning shift (IRR = 0.65, p = 0.001) and evening shift (IRR = 0.69, p = 0.011) was significantly lower than that in the night shift. Conclusion Estimating the prevalence and types of medication errors and identified risk factors allows for more targeted interventions. According to the findings of the study, training nurses, adopting an evidence-based care approach and creating interaction and coordination between nurses and pharmacists in the hospital can play an effective role in reducing the medication error of nurses. However, further research is needed to evaluate the effectiveness of interventions to reduce the prevalence of medication errors.